Computational modeling of the direct hydride transfer mechanism for the MAO catalyzed oxidation of phenethylamine and benzylamine: ONIOM (QM/QM) calculations - ERDEM, SAFİYE (SPRINGER WIEN, 2013)
Monoamine oxidases are two isozymic flavoenzymes which are the important targets for drugs used in the treatment of depression, Parkinson and Alzheimer's diseases. The catalytic reaction taking place between the cofactor FAD and amine substrate is still not completely understood. Herein we employed quantum chemical methods on the recently proposed direct hydride transfer mechanism including full active site residues of MAO isoforms in the calculations. Activation free energy barriers of direct hydride transfer mechanism for MAO-A and MAO-B were calculated by ONIOM (our own n-layered integrated molecular orbital + molecular mechanics) method with QM/QM (quantum mechanics:quantum mechanics) approach employing several density functional theory functionals, B3LYP, WB97XD, CAM-B3LYP and M06-2X, for the high layer. The formation of very recently proposed alpha C-flavin N5 adduct inside the enzyme has been investigated. ONIOM (M06-2X/6-31+G(d,p):PM6) results revealed that such an adduct may form only in MAO-B suggesting slightly different hydride transfer mechanisms for MAO-A and MAO-B.
Keywords: Enzyme modeling; Flavoenzymes; Hydride transfer; Enzyme mechanism; Dispersion-corrected DFT; MONOAMINE-OXIDASE-B; DENSITY FUNCTIONALS; AMINE-OXIDATION; BOND-CLEAVAGE; ACTIVE-SITE; DISPERSION; RESOLUTION; INSIGHTS; ANALOGS; RAT